How green is your smartphone? - Maxwell, Richard 1957- (Polity, 2020)
"Every day we are inundated by propaganda that claims life will be better once we are connected to digital technology. Poverty, famine, and injustice will end, and the economy will be 'green'. All anyone needs is the latest smartphone. In this succinct and lively book, Maxwell and Miller take a critical look at contemporary gadgets and the systems that connect them, shedding light on environmental risks. Contrary to widespread claims, consumer electronics and other digital technologies are made in ways that cause some of the worst environmental disasters of our time - conflict-minerals extraction, fatal and life-threatening occupational hazards, toxic pollution of ecosystems, rising energy consumption linked to increased carbon emissions, and e-waste. Nonetheless, a greener future is possible, in which technology meets its emancipatory and progressive potential. How Green is Your Smartphone? encourages us to look at our phones and tablets in a whole new way, and is important reading for anyone concerned by the impact of everyday technologies on our environment"--Cover
Keywords: Smartphones; Electronic industries; Environmental justice